Detection of Protozoa Intestinal Zoonotic in Madura Cattle in Bangkalan Madura Regency - Sunarso, Agus; Poedji Hastutiek; Mufasirin (Journal of Parasite Science, 2025)
The study aimed to detect the protozoan intestinal zoonotic that can potentially be a strategic disease in Madura cattle. The prevalence of the disease was linked to the sex and age of cattle in Bangkalan Regency. Cattle feces samples were collected 400 samples from eight sub-districts in Bangkalan District. Feces were examined natively, sedimentation, and floating. The species of protozoa was determined based on its morphology. The prevalence was expressed in percent, the study results were presented in figures and tables. The prevalence of protozoan intestinal zoonoses was 27.75%. The highest rate was found in Kwanyar (50%). Four species, namely Blastocystis hominis, Balantidium coli, Entamoeba coli, and Giardia bovis. In a single infection, B. hominis as the most protozoa was found to infect 85 cattle in eight sub-districts, B. coli was found in 16 cattle in four sub-districts and E. coli in 5 cattle in Kwanyar. A total of 107 samples were found to be infected with a single protozoan species, while 4 samples contained two species. The infection rate in bulls was 26.66%, which was slightly lower than in cows at 28.06%. Protozoan infections were more common in cattle aged 6 months to 2 years (42.4%) and those under 6 months (35.8%) compared to cattle over 2 years old (16.4%). This study confirmed the presence of intestinal zoonotic protozoa in cattle in Bangkalan District. Further research is needed to assess the prevalence of protozoa, identify risk factors, and analyze their geographic distribution, for developing effective prevention and control strategies.